Administration of Special Needs Education Programme in Federal Capital Territory, Abuja: Problems and Solutions - Ogunode Niyi Jacob; Deborah Jegede; Ajape Temitope Solomon (Jurnal Sinestesia, 2020)
In Nigeria, Special Needs Education programme is a very special programme designed for persons with disabilities and persons with Special Needs. The Special Needs Education programme is being implemented in all the 36 states and in Federal Capital Territory, Abuja. The administration of the Special Needs Education programme faces many problems across the country. This article discusses the problems facing the administration of special needs education programme in Federal Capital Territory, Abuja. Secondary data was used to support the points raised in the article. This study sourced secondary data from print material and online publication by recognized institutions and individual author. Special needs programme in Federal Capital Territory (FCT) faced with the problems of; inadequate funding, inadequate infrastructural facilities, inadequate professional teachers, poor supervision, inadequate instructional materials, poor planning, institutional corruption, lack of data to plan and poor implementation of Special needs education policies. To solve these challenges, this article recommends: that the government should increase the funding of Special need education, provide adequate infrastructural facilities, employment of more professional teachers, provision of adequate instructional materials, ensure effective supervision and planning of the special need programme.